On the Ro - Vibrational Study of "Hot" Transitions in C2D4:The v7 + v10 - v10 and v10 + v12 - v10 bands - Fomchenko A. L. Anna Leonidovna; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Sklyarova E. A. Elena Aleksandrovna; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann (Poster session J, 2016)
Title screen